Experimental and molecular dynamics studies of plasma-HDPE surface interactions - Mella, Aubrey Faith M.
Modification of high-density polyethylene (HDPE) substrates has been conducted to gain insight into the interactions between the active species from a plasma and the first few layers of the surface. A capacitively-coupled 13.56 MHz radio frequency plasma etcher was developed for HDPE surface modification. Effects of the experimental parameters such as etching time (0.5-3 min), incident plasma power (50-100 W), and type of gas used (Ar and 02) were investigated. Water contact angles revealed an increase in the hydrophilicity of an inherently hydrophobic HDPE after plasma exposure. Likewise, an enhancement of up to 65.5 percent of the surface free energy was observed compared to as-received samples. Changes in surface chemistry was evident when reactive O2 plasma was used. Fourier-transform infrared spectral measurements suggest an increase in the number of reactive sites through the presence of unsaturated carbon on the HDPE surface. On the other hand, surface chemistry changes from x-ray photoelectron spectroscopy measurements under Ar plasma irradiation showed an increase in the amount of surface functional groups as suggested by an increase in O content (+14 percent) and increase in C-O bonds (+9.5 percent). Surface profile measurements using an atomic force microscope revealed an increase in rms roughness after plasma treatment as well as the formation of broad peaks (kurtosis<3.0). Concurrently, a numerical scheme was implemented to gain insight into the atomistic interactions between an active particle from the plasma and the atoms on a surface. Molecular dynamics studies using LAMMPS (Large-scale Atomic/Molecular Massively Parallel Simulator) have been performed to simulate the energetic interactions between an Ar ion and the HDPE surface. Initial substrate conditions and thermostat of crystalline HDPE were modeled while incident Ar ion energies were based on actual discharge conditions and plasma sheath dynamics. Interatomic potentials for hydrocarbons and Ar interactions were employed using empirical bond order and the Lennard-Jones potential. Surface profiles of HDPE after 171 Ar injection cycles showed that sputtered C and H atoms were dependent on the incident energies of Ar. H atoms were preferentially sputtered E to the weaker interaction between C and H atoms compared to the HDPE C to C backbone. Calculated surface roughness of the model were found to increase with increased energies which was also observed experimentally. The simulations also confirmed that Ar-HDPE interactions only affect the surface or the first three layers of HDPE, while the bulk properties of the HDPE are not affected by the low-energy ion bombardment. This study was able to demonstrate the synergistic relation between experimental work and numerical modeling in plasma-surface interactions and how the latter approach can be used to design material surfaces. Tuning the nanoscale features of HDPE using gaseous discharges finds several industrial applications. One application of plasma-modified HDPE is to inhibit or delay biofilm formation, an inherent problem in the water industry. Initial biofilm count during the early stages of P. aeruginosa adhesion on the HDPE were investigated. After plasma treatment, colony forming units (CFU/in2) decreased. The lowest colony forming units (CFU/ins) were observed when the HDPE is treated with O2 plasma at 50 W power for 3 min. A decrease of 8.62 percent in initial biofilm formation was observed. The decrease in biofilm count can be attributed to several factors such as increase in hydrophilicity, incorporation of functional groups, and increase in surface roughness. These changes on the HDPE surface were supported by plasma treatment studies both experimentally and numerically.